1979
DOI: 10.1159/000122889
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Alterations of Endorphin Levels in Rat Pituitary

Abstract: Endorphin (END) levels in rat pituitary were assessed with the opiate receptor binding assay. Procedures reported to alter hormone secretion from END-rich intermediate or anterior lobes were examined for their effect on END content. Lesions of the paraventricular nucleus (PVN) had no significant effect on END content. Ingestion of 2% NaCl reduced END levels in a significant majority of the animals. Suckling, a natural physiological stimulus, significantly elevated neurointermediate lobe END. Footshock and immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

1980
1980
1987
1987

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 32 publications
4
8
1
Order By: Relevance
“…The temporal difference in the reduction of ir-pEP content found in AP and N-IL following foot shock supports previous observa tions [2] that ir-pEP content in these two tissues can be selec tively affected, and that the synthesis [27] and the release [32,37,38] of the peptide in AP and N-IL are affected by different factors. It is, however, not clear to what extent N-IL ir-PEP is released into the general circulation under basal or stressful conditions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The temporal difference in the reduction of ir-pEP content found in AP and N-IL following foot shock supports previous observa tions [2] that ir-pEP content in these two tissues can be selec tively affected, and that the synthesis [27] and the release [32,37,38] of the peptide in AP and N-IL are affected by different factors. It is, however, not clear to what extent N-IL ir-PEP is released into the general circulation under basal or stressful conditions.…”
Section: Discussionsupporting
confidence: 87%
“…It is perhaps interesting that similar results for AP content of PEP have also been found by opiate re ceptor assay [2], suggesting that both P-LPH and p-EP are affected simultaneously by acute stress. The simplest expla nation for the changes of ir-PEP in AP is that foot shock en hances the release of ir-pEP from the AP into circulation at a rate exceeding its synthesis, leading eventually to a net de pletion of its content.…”
Section: Discussionsupporting
confidence: 70%
“…Reduction in N-IL content of PEP and ACTH bio logical activities have been shown previously in rats subject ed to various stress procedures including immobilization [5], hypertonic saline ingestion [1,33] and breast feeding [1]. In electron microscopic studies [34], the reduction of ACTH in N-IL after immobilization has been shown to be consist ent with the depletion of secretory vesicles in the pituitary cells, suggesting significant excretion of the peptide.…”
Section: Discussionmentioning
confidence: 73%
“…A receptor-binding assay of morphine-like activity (MLA) was performed according to Baizman et al [1], A 2% rat brain homogen ate (prepared as described by Dr. B. Cox, personal commun.) was incubated at room temperature with 3H-etorphine (Amersham, TRK-476) in the presence of samples of perifusion medium or the naloxone-HCI standard (Endo Labs).…”
Section: Hormone Assaysmentioning
confidence: 99%